KAJIAN TAFSIR DALAM KITAB SAHIH BUKHARI - Muhsin al-Haddar (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2015)
This paper explains that Imam Bukhari in the book Shahih his interpretations have come from the hadiths. There is a special chapter in his book namely chapter of Interpretation. This paper wants to show that Imam Bukhari also could interpret the hadith sources. In this case writer would like to explain how the methods of interpretation. Moreover, whether Imam Bukhari as interpreter is the same with classical interpreters that using athar method. This is what will be revealed in this paper. To see this method the writer compared it with interpretation that written by Ibn Jarir al-Tabari and Ibn Kathir. The reason for using this interpretation because the two interpretations used athar method in explaining its interpretation. The Results of this comparison explaining that Imam Bukhari also can be regarded as a classical interpreter who explain tafseer using athar interpretation methods. Then, the manhaj used is bil ma'thur